Control of Acute Dengue Virus Infection by Natural Killer Cells - Petitdemange, Caroline; Wauquier, Nadia; Rey, Juliana; Hervier, Baptiste; Leroy, Eric; Vieillard, Vincent (Frontiers in Immunology, 2014)
Dengue fever is the most important arthropod-borne viral disease worldwide, affecting 50 to 100 million individuals annually. The clinical picture associated with acute dengue virus (DENV) infections ranges from classical febrile illness to life-threatening disease. The innate immunity is the first line of defense in the control of viral replication. This review will examine the particular role of natural killer (NK) cells in DENV infection. Over recent years, our understanding of the interplay between NK cells and viral pathogenesis has improved significantly. NK cells express an array of inhibitory and activating receptors that enable them to detect infected targets while sparing normal cells, and to recruit adaptive immune cells. To date, the exact mechanism by which NK cells may contribute to the control of DENV infection remains elusive. Importantly, DENV has acquired mechanisms to evade NK cell responses, further underlining the relevance of these cells in pathophysiology. Hence, understanding how NK cells affect the outcome of DENV infection could benefit the management of this acute disease.